Current Issues in the regulation of deceptive advertising: Some consequences for South Africa - Shahida Cassim; Robert Langton (South African Journal of Business Management, 1996)
The dramatic political changes that have recently taken place in South Africa have focussed attention on the adequacy of the existing controls on deceptive advertising. On the one hand, there is a recognition that, due to the limited access to educational opportunities in the past, the majority of South African consumers might be particularly susceptible to deceptive advertising and thus existing controls might need to be tightened. On the other hand, the new interim Constitution has elevated freedom of speech and access to the media to the status of fundamental rights to which other controls are subject. These rights are likely to provide a basis to challenge both the existing controls and any attempt to tighten the control of advertising content. This article outlines the controls on deceptive advertising that currently exist in South Africa. It then examines the current debate surrounding the need for and the efficacy of such controls.
Keywords: 650